High-velocity suspension flame sprayed (HVSFS) soda-lime glass coating on titanium substrate: Its bactericidal behaviour. Issue 10 (August 2016) - Díaz, L.A.; Cabal, B.; Prado, C.; Moya, J.S.; Torrecillas, R.; Fernández, A.; Arhire, I.; Krieg, P.; Killinger, A.; Gadow, R.
Abstract: Antimicrobial coatings based on a family of non-toxic, antimicrobial glass that belongs to the SiO2 -Na2 O–Al2 O3 –CaO–B2 O3 system, were thermally sprayed on titanium plates by high velocity suspension flame spraying (HVSFS). Atomized glass microspheres (<10 μm) were dispersed in water in order to prepare suitable suspensions for the HVSFS process. Spraying antimicrobial atomized glass microspheres results in mechanical stable coatings with a layer thickness ∼25 μm. The process does not compromise the antimicrobial activity of the glass and it does not cause it to significantly crystallize. The coatings were proven to be antimicrobial versus Escherichia coli, Staphylococcus aureus and Candida krusei . This raises the possibility for its application on titanium-based implants, for instance in dental prosthesis, preventing at the same time infections and implant corrosion.